ON AN EIGENVALUE PROBLEM - Arabyan, M. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
In the paper an eigenvalue problem for a system of equations with unsummable coefficients is discussed. To solve the problem special weight functional spaces are introduced. For these spaces embedding theorems are proved. The existence and uniqueness of a boundary value problem is considered. The existence of eigenvalue problem solution is proved.